Human papillomavirus research trends in Latin American compared to high income countries - Moya-Salazar, Jeel Junior; Rojas-Zumaran, Victor (Revista Colombiana de Obstetricia y Ginecología, 2017)
Objective: This paper is intended to be a reflection on the trends in Human Papilloma Virus (VPH) research in Latin America, compared to high income countries. Materials and methods: Answers are provided regarding HPV in terms of frequency, research trends, education programmes for patients and healthcare staff, and preventive strategies. An extensive review was conducted of the published research and of the studies presented during the I South American Meeting on HPV. Results: Research work in HPV is focused on basic and applied studies on HVP and cervical cancer (CC). There are limitations to scientific development in our region compared to high income countries, and this is reflected in disease prevalence and vaccination rates. Prevention programs at each level are undergoing slow transformations as the natural hurdles of the region are overcome. Conclusion: The impact of HPV infection and cervical cancer is huge in Latin America, requiring the development of public policy and organized preventive interventions.